Propriedades ópticas não lineares de cristais líquidos dopados com azocorantes nas proximidades da transição nemática - esmética-A de primeira ordem. - Souza Júnior, Pedro Juvencio de (2013)
Nonlinear optical properties of liquid crystals have been extensively studied due to their enormous potential application in different electro-optical devices. These systems exhibit a great variety of phenomena associated with their huge nonlinear optical response, such as photorefractive effect, degenerate wave mixing, and solitary waves propagation. In particular, the addition of azo-dyes in nematic liquid crystals has been observed to enhance the nonlinear optical response of these systems which is mainly associated with an anomalous reorientation of the optical axis defined by nematic director. Although several works have been devoted to the study of the reorientation of optical axis in nematic liquid crystals, such phenomenon has not been explored in the smectic systems so far. By using the time-resolved z-scan technique, in this work we study the nonlinear optical response of smectic liquid crystals (8CB) doped with an azo dye (Sudan Black B). In samples presenting a homeotropic alignment, our results show that the sign of the nonlinear optical response in the smectic phase is high sensitive to the dye concentration and the sample temperature. More specifically, we observe that the director reorientation induced by the dye photoisomerization is suppressed in the smectic phase for low dye concentrations. The effects of an external electric Field are also investigated. The present results are discussed in the light of Helfrich- arault effect which predicts a suppression of the director reorientation in the smectic phase due to the high energy cost associated with the compression of smectic layers.